Constituent physical ingredients of rape: a proposal for law reform - Mohamad Yunus, Mohamad Ismail (The Malaysian Current Law Journal Sdn Bhd, 2004)
Historically, the law of rape was concerned particularly with the theft of virginity, reflecting a preoccupation with the protection of virgins from rape, abduction and forced marriage. And basically, before an accused can be convicted of any serious offence, it must be proved that he performed some act that is prohibited by the law and that he did so with a spesific state of mind. The first of these ingredients, the external (physical) element of the crime, is known as the actus reus; the second, the mental element, as the mens rea. The prosecution bears the burden of proving to the court, beyond a reasonable doubt, that the accused person performed the act constituting the actus reus of the offence and did so with the necessary mens rea. Consequently, in analysing a serious crime like rape, both ingredients must be seriously considered. With reference to s. 375 of the Penal Code, it is noted that the actus reus of rape is "sexual intercourse" by a man with a woman who "does not consent" to the act. Therefore, the main focus of this research is to analyze the basic elements of actus reus only with special emphasis on its definition, nature, scope, application and current legal development from various jurisdictions.